The LITAS payment System: its Present and Prospects - Bikas, Egidijus; Novickytė, Lina (Ekonomika, 2008)
The object of the article is the role of payment systems in interbank settlements and a set of the system activity refinement. The LIT AS payment system started its operation on 19 January 2004. LITAS is designed to process payment instructions in real time and at a designated time. The system processes credit and debit transfers. The Bank of Lithuania is the owner and the operator of the system. LIT AS provides the cash leg of security transactions in real and at designated time following the DvP (delivery versus payment) principle. It also establishes a possibility for other payment systems to perform settlements through the accounts of their participants with the Bank of Lithuania. Various credit, liquidity and operational risk management measures are applied in the LIT AS system. The successful activity of the payment system LITAS was suspended on 28 January 2007. Two new payment systems - LITAS-RLS and LITAS MMS - started operating on 29 January 2007. This decision was related with the aspiration of the Bank of Lithuania to integrate the new systems into the European payment system TARGET 2. The payment system LITAS-RLS was designed for the realtime processing of payment orders in litas, initiated by its participants. It also offers conditions for the final settlement of ancillary systems. All participants of the system may initiate credit transfers. The LITAS-MMS payment system was designed for the processing of payment orders in litas initiated by its participants at a designated time. Although the LITAS-MMS system is oriented towards the retail payment market, it performs the function of a clearing house. The SWOT analysis carried out by the LITAS payment system showed that the principal advantages of the system include its conformity to the international practice, low unit prices of services, an effective risk management system, domination of the system itself in the market and a high quality of services. Its imperfections include a lack of public information, unclear future of the system and a considerable variability. The most important potentials of the system include the continuity of operation, the growing market and the exclusivity of the image. The principal dangers that may menace the LIT AS system include the liquidation of the system, possible new competitors, pressing of market participants. Payment systems, Bank of Lithuania statistics information about payment transfers, their structure and dynamics, real time and designated time transfer cumulative curves, which helps to regulate the money flows in the payment system. An analysis has shown that the operation of the LITAS system was successful. This fact encourages stating that the direction of the activities chosen by the operator of the system was correct. The article presents final remarks about the Lithuanian LITAS payment system and suggestions how to improve its activity and safety.